UMP observes qurban and aqiqah, 7 cows slaughtered - Nor Salwana, Mohammad Idris (2022)
PAYA BESAR, 15 July 2022 – As is common in celebrating Aidiladha year after year, the Islamic and Human Development Centre (PIMPIN), Universiti Malaysia Pahang (UMP) also organised the Ibadah Korban dan Akikah 1443H programme at the UMP Gambang Campus Mosque.